PANDANGAN ONTOLOGIS MANAJEMEN KERJASAMA SEKOLAH DAN MASYARAKAT - Asep Kurniawan (IAIN SYEKH NUR JATI, 2020)
This study aimed to reveal in-depth the ontology view of school and community cooperation management. The method of this study was a literature qualitative method. The research process was done descriptively and critically by focusing on the sharpness of the analysis on relevant and sources data. Research prioritized existing theories and concepts, then interpreted based on references that lead to discussion. Data analysis techniques were performed using content analysis. The results showed that the collaboration management of school and community was carried out through the delivery of information and partnerships carried out through the stages of fact finding, planning, implementing, and evaluating by educational institutions towards the community. The collaboration management of School and community was carried out to realize the educational goals.